2013
DOI: 10.1016/j.jacc.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Disparities in the Use of Cardioprotective Medications Among Patients With Peripheral Artery Disease

Abstract: Objective Examine disparities in use of cardioprotective medications in treatment of peripheral artery disease (PAD) by socioeconomic status (SES). Background PAD is associated with increased cardiovascular risk and is more prevalent among those of lower SES. However, the use of guideline-recommended secondary preventive measures for the treatment of PAD across diverse income subgroups and the influence of practice site on potential treatment disparities by SES are unknown. Methods Within the National Card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In addition, despite recent work from Subherwal and colleagues demonstrating disparities in the use of cardiovascular medications among patients with PAD, we did not find that medication use affected the relationship between SES and prevalence of PAD. 21 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, despite recent work from Subherwal and colleagues demonstrating disparities in the use of cardiovascular medications among patients with PAD, we did not find that medication use affected the relationship between SES and prevalence of PAD. 21 …”
Section: Discussionmentioning
confidence: 99%
“…47 Furthermore, neighborhood income may represent geography and distance to hospitals. However, numerous previous studies have done the same 4849 and prior evaluation has found disparities at both the ZIP code and individual level of analysis. 50 With regards to inequalities in PCI use, it is important to emphasize that we evaluated only patients presenting to the hospital with ACS, which does not include elective or outpatient PCI cases.…”
Section: Discussionmentioning
confidence: 99%
“… 32 In another study of patients with peripheral artery disease, patients living in low socioeconomic status areas, as defined by median household income, were less likely to receive statins than patients living in higher socioeconomic status areas. 28 Racial/ethnic differences in exercise participation, smoking and obesity have also been reported. 25 33 However, our work extends and broadens the findings of these studies because (1) our study focused on actively symptomatic patients, whose presentation may be attributable to gaps in prevention and (2) we simultaneously accounted for a wider range of sociodemographic characteristics.…”
Section: Discussionmentioning
confidence: 99%